Living Property Market in Terms of Ownership and Lease in the Given Region - Pasko, Igor; Semenenko, Vadim; Procházka, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The thesis examines the residential property market in the Czech Republic through the perspectives of homeownership and lease, offering a data-driven assessment of current market dynamics and suggesting future development trajectories. The research integrates interviews with real estate executives that offer up-to-date insights to the living property market environment. By analyzing historical transformations, present economic and regulatory conditions, as well as key indicators, the study identifies and explains factors influencing market behavior. Additionally, a mathematical decision-making model is introduced to evaluate the economic viability of homeownership in comparison with tenancy. The model lays the basis for further specification and practical implementation, such as providing potential dwellers with a rational framework for navigating housing decisions. The study underlines the need for more balanced housing strategies, including improved social housing initiatives, diversification of the development operations across the country and streamlined development regulations. The findings of the thesis highlight the increasing relevance of rental sectors amid rising property prices and limited housing supply, while also providing projections for further market development.
Vedoucí práce: Vadim Semenenko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses